The Role of Karang Taruna in Preserving Local Culture in Aik Bual Village, Kopang Subdistrict, Central Lombok Regency - Lalu Muhammad Zia'ul haq; zubairfkip8@gmail.com; M. Samsul Hadi (STKIP Taman Siswa Bima, 2025)
This study aims to explore the role of the Karang Taruna in Aik Bual Village in preserving local culture, as well as the challenges they face. The research employs a qualitative method with an ethnographic approach. Data collection was conducted through direct observation, in-depth interviews, and documentation. The research subjects include the village government, community leaders, and members of Karang Taruna. The findings indicate that Karang Taruna plays an active role in local cultural activities such as Bekerase, Nyelametan, and Bejambek. Their involvement includes organizing committees, mobilizing youth participation, providing material and logistical support, initiating cultural events, disseminating cultural information and education, and safeguarding the existence of local traditions. However, they face several challenges in preserving local culture, such as low interest among younger generations, the influence of globalization, limited cultural preservation programs, perceptions of cultural practices as conflicting with religious teachings, and the lack of regeneration and supporting facilities. Therefore, creative strategies, collaborative approaches, and institutional support are needed to ensure sustainable cultural preservation.